Conventional Money Market Practices and Prices in Conventional Money Market - Iir Tsamrotur Rofa; Muhammad Ikhsan Harahap (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The money market has an important role in the economy. For those who have a surplus of funds, the money market is an important means of investment. Meanwhile, for those who need funds, the money market is an important solution to overcome the problems they face. In today's modern era, transactions that occur in the money market are generally carried out directly through the telephone electronic data link media. These transactions are called Over the Counter (OTC) transactions. The actors can carry out transactions on the domestic (domestic) or foreign market that do not require a real market form. Transactions on the money market can be carried out 24 hours a day around the world, allowing fund owners to put their capital in markets that provide high interest rates. Meanwhile, borrowers can look for loans in the market that offers the lowest interest rates. Prices in the Conventional Money Market are usually expressed as a percentage that represents the income (return) associated with the use of money for a certain period of time